Effect of Hydrotropism on Root System Development in Soybean (Glycine max): Growth Experiments and a Model Simulation - Tsutsumi, Daizo; Kosugi, Ken'ichiro; Mizuyama, Takahisa (Journal of plant growth regulation, 2002)
To observe root system development, soybean plants (Glycine max) were grown in root boxes that were set horizontally to reduce the effect of gravity. Along with the root system development, the two-dimensional distribution of soil water content in the root boxes was measured continuously by the time domain reflectometry (TDR) method. Root system development and its morphological architecture were strongly affected by the positions of the water supply. It is suggested that root hydrotropism plays the dominant role in root system development. In addition to root hydrotropism, the importance of root compensatory growth is suggested. A combined model of root system development and soil water flow considering root hydrotropism and compensatory growth was used to simulate root system development and soil water flow. The morphological architecture of root systems and the distribution of soil water content obtained in the experiment were successfully explained by the model simulation. These results confirmed that root hydrotropism and compensatory growth are dominant factors in root system development under a reduced effect of gravity. The validity of the model was confirmed, and its applications for various purposes were suggested.